Application of Creative Multimedia Technology in Banking - Vijayan, Paramsothy (2003)
This research is one of the few studies in Malaysia to demonstrate empirically a parsimonious link between customer's value cluster, human computer interface and technology acceptance theories. Impications for further research include the application of the research objective to other services and further qualitative research to complement this research.